Allicin improves carotid artery intima-media thickness in coronary artery disease patients with hyperhomocysteinemia - Liu, De-Shan (Exp Ther Med, 2017)
Homocysteine (Hcy) is an important and independent risk factor for atherosclerotic diseases, such as coronary artery disease and ischemic cerebrovascular disease. Increased carotid artery intima-media thickness (IMT) is a non-invasive marker of systemic atherosclerosis. Allicin treatment may decrease serum Hcy levels and improve impaired endothelial function in rats with hyperhomocysteinemia (HHcy). The present study hypothesized that allicin has an anti-atherosclerotic effect in coronary heart disease and tested the effects of allicin treatment on carotid artery IMT and plasma Hcy levels in coronary heart disease patients with HHcy. Sixty-two coronary heart disease patients with HHcy were randomly divided into an allicin group and a control group. All patients underwent diagnostic assessment, plasma Hcy assay, blood lipid measurement and B-mode ultrasound of the carotid artery prior to and after treatment. Plasma Hcy levels were determined by high-performance liquid chromatography and fluorescence detection. Carotid artery IMT was calculated using an automated algorithm based on a validated edge-detection technique. After 12 weeks, significant decreases in carotid artery IMT, plasma Hcy levels, total cholesterol and triglycerides were observed in the allicin group (all P<0.05), and the decreases in the allicin group were significantly greater than those in the control group (all P<0.01). These findings suggested that reducing plasma Hcy levels may be useful for preventing the generation and development of atherosclerosis in patients with coronary heart disease. Allicin was able to decrease Hcy levels, total cholesterol and triglycerides as well as carotid artery IMT.